PENGARUH PENERAPAN METODE COURSE REVIEW HORAY DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 LEMBAH GUMANTI - Mursyidah, Mursyidah; Rahmi, Rahmi; Lovia, Lita (STKIP PGRI Sumbar, 2013)
This research is based on opinions of the eleventh grade students ofÂ Natural Science at SMAN 1 Lembah Gumanti that mathematics is a difficult, boring lesson. This is supported by the fact that their understanding of the mathematics concept is still low. This research is aimed at knowing the development of the studentsâ understanding of the mathematics concept who are treated by using Course Review horay method in combination with quiz and finding out whether the understanding of the mathematics concept of the students who are treated by using Course Review horay method in combination with quiz is better than the ones who are treated by using conventional teaching method. This research is an experimental research with random research design towards the subject. The instruments of this research were quiz and post-test. The test was given in the form of essay with reliability of the test equals 0.96. based on data analysis, it was found that the average of the experimental class studentsâ understanding of the mathematics concept was 79.75, higher than the control class who got only 74.24. based data analysis using MINITAB, it is found that P-Value = 0.037, less than . the H1 is accepted. So, it can be concluded that the understanding of the mathematics concept of the student who are treated by using Course Review Horay method in combination mith quiz is better than the ones who are treated by using conventional teaching method with the confidence level of 95%.